Effect of TiC Coating Thickness on Carbon Fiber Surface on Microstructure and Properties of Aluminum Matrix Composites - Hongkui Zhang; Yipeng Lan; Xiangjia Meng; Wenjie Liu; Guanglong Li (Metals)
In this paper, the synthesis of TiC-coated carbon fibers (TiC-CFs) with varying thicknesses is achieved through the manipulation of the molten salt reaction, along with the fabrication of TiC-coated carbon fiber-reinforced aluminum matrix (TiC-CF/Al) composites via the vacuum pressure infiltration technique. The results show that modulating the holding time of the molten salt reaction significantly enhances the wettability between the carbon fiber (CF) and the aluminum, thereby augmenting the mechanical integrity of the composite materials. Should the holding time be excessively short, the coating on the CF surface develops an uneven distribution, and its efficacy in obstructing the direct interaction with the aluminum is inadequate. As the holding time prolongs, the TiC coating thickens, achieving a comprehensive coverage after 2 h of holding. The presence of a pristine TiC coating on the CF surface not only optimizes the wettability with the aluminum melt but also mitigates the reaction between the CF and aluminum. However, an excessively thick coating not only reduces the strength of the fibers, due to excessive reactions, but also makes the coating prone to detachment during the preparation process due to stress. At a holding time of 3 h, the tensile strength of the CF/Al composite material reaches its highest value, with a tensile strength of 103.93 MPa and an impressive 72.35% enhancement over that of the aluminum.